2021
DOI: 10.3390/ijms22094444
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum ATG-K2 and ATG-K6 Ameliorates High-Fat with High-Fructose Induced Intestinal Inflammation

Abstract: Obesity has become a worldwide health problem, and many significant inflammatory markers have been associated with the risk of side effects of obesity and obesity-related diseases. After a normal diet or high-fat diet with high-fructose water (HFHF) for 8 weeks, male Wistar rats were divided randomly into four experimental groups according to body weight. Next, for 8 weeks, a normal diet, HFHF diet, and HFHF diet with L. plantarum strains ATG-K2 or ATG-K6 were administered orally. Compared to the control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
(46 reference statements)
2
7
0
Order By: Relevance
“…The present study found that L. plantarum ATG-K2 decreased TNF-α mRNA expression levels in the small intestine and serum TNF-α levels. This finding is supported by previous reports that L. plantarum ATG-K2 reduced the expression levels of inflammatory cytokines such as TNF-α and IL-6, and NF-κB in the small intestine of high-fat and high-fructose diet fed rats [22]. These results indicate that L. plantarum ATG-K2 relieves intestinal inflammation, contributing to its protective effect against HFD-induced obesity.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The present study found that L. plantarum ATG-K2 decreased TNF-α mRNA expression levels in the small intestine and serum TNF-α levels. This finding is supported by previous reports that L. plantarum ATG-K2 reduced the expression levels of inflammatory cytokines such as TNF-α and IL-6, and NF-κB in the small intestine of high-fat and high-fructose diet fed rats [22]. These results indicate that L. plantarum ATG-K2 relieves intestinal inflammation, contributing to its protective effect against HFD-induced obesity.…”
Section: Discussionsupporting
confidence: 89%
“…We have previously proven Lactiplantibacillus plantarum ATG-K2 isolated from fermented cabbage, a traditional Korean food [ 20 ], possesses a beneficial effect on non-alcoholic fatty liver disease and intestinal inflammation in high-fat and high-fructose diet fed rats [ 21 , 22 ]. However, no previous study has examined the anti-obesity effects of this probiotic strain.…”
Section: Introductionmentioning
confidence: 99%
“…The relieving effect of L. plantarum on intestinal inflammation has been reported in other studies [ 56 , 57 ]. The gene expression and production of anti-inflammatory factors (IL-10, TGF-β1, and TGF-β2) increased in Caco-2 cells and a DSS-induced mouse model [ 58 , 59 ].…”
Section: Discussionsupporting
confidence: 70%
“…Studies suggest that the lactobacilli population decreases with age, and supplementation of probiotic lactobacilli to older adults improves their health by modulating gut microbiota composition, enhancing immunity and gut health [ 19 , 20 , 21 ]. Previous reports indicated the role of lactobacilli on longevity with different features of healthy aging such as resistance to oxidative stress and toxicity, protection against pathogenic infections, reducing fat accumulation, improving cognition, alleviating inflammation, metabolic disorders, and neurodegenerative diseases [ 12 , 13 , 14 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. However, a single microbe affecting these diverse features of healthy ageing will increase the acceptance and marketability as a next generation probiotic.…”
Section: Introductionmentioning
confidence: 99%